Adenovirally Delivered Enzyme Prodrug Therapy with Herpes Simplex Virus–Thymidine Kinase in Composite Tissue Free Flaps Shows Therapeutic Efficacy in Rat Models of Glioma. Issue 2 (February 2015) - Seth, Rohit; Khan, Aadil A.; Pencavel, Timothy D.; Wilkinson, Michelle J.; Kyula, Joan N.; Simpson, Guy; Pandha, Hardev; Melcher, Alan; Vile, Richard; Harris, Paul A.; Harrington, Kevin J.
<x xml:space="preserve">Abstract</x> Introduction: Free flap gene therapy exploits a novel therapeutic window when viral vectors can be delivered into a flap ex vivo. The authors investigated the therapeutic potential of an adenovirally-delivered thymidine kinase/ganciclovir prodrug system expressed following vector delivery into a free flap. Methods: The authors demonstrated direct in vitro cytotoxicity by treating a panel of malignant cell lines with the thymidine kinase/ganciclovir system and demonstrated significant cell kill proportional to the multiplicity of infection of adenoviral vector expressing thymidine kinase. Bystander cytotoxicity was demonstrated using conditioned media from producer cells (expressing adenovirally-delivered thymidine kinase and treated with ganciclovir) to demonstrate cytotoxicity in naive tumor cells. The authors investigated the effect of adenoviral vector expressing thymidine kinase/ganciclovir therapy in vivo, using models of microscopic and macroscopic residual disease in a rodent superficial inferior epigastric artery flap model. Results: The authors observed retardation of tumor volume growth in both microscopic (p = 0.0004) and macroscopic (p = 0.0005) residual disease models and prolongation of animal survival. Gene expression studies demonstrated that viral genomic material was found predominantly in flap tissues but declined over time. Conclusions: The authors describe the utility of virally delivered enzyme/prodrug therapy, using a free flap as a vehicle for delivery. They discuss the merits and limitations of this approach and the unique role of therapeutic free flaps among reconstructive techniques available to the plastic surgeon.